Effectiveness of Core Stability Exercise in Physiotherapy Approach to Improve Cardiorespiratory Fitness in College Students - Pradita, Angria; Halimah, Nurul (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: Physical fitness, especially cardiorespiratory fitness, is an important factor in supporting students' health and academic performance. However, an increase in sedentary lifestyles has led to a decrease in physical fitness levels in university students. This study evaluates the effectiveness of the Core Stability Exercise (CSE) program in improving the cardiorespiratory fitness of university students, using a combination of bicycle crunch and mountain climber as the main exercises. This exercise is one of the physiotherapy exercise methods that focuses on strengthening core muscles, which not only improves body stability but also contributes to improving cardiorespiratory capacity through diaphragm activation and postural control. This study aimed to evaluate the effectiveness of CSE in improving the physical fitness of university students using a one-group pre-post-test quasi-experimental design. Methods: A total of 27 students underwent the bicycle crunch and mountain climber exercise program for eight weeks with a frequency of three times a week. Cardiorespiratory fitness was measured using the Harvard Step Test, and the results of statistical analysis with the Wilcoxon test showed a significant increase (p < 0.05) after the intervention. Results: The results of this study indicate that Core Stability Exercise is an effective exercise method in improving the cardiorespiratory fitness of college students. Conclusion: Therefore, this exercise is recommended as part of a preventive physiotherapy program to improve the health and fitness of students in the academic environment.